VASCULAR GRAFT INFECTIONS — A HISTORICAL REVIEW - Gouveia e Melo, Ryan (2020)
Vascular graft infections are still to date a complex medical challenge. The evolution of the hospital flora and development of the vascular surgery field has led to a change in the reality of these infections, making it important to know their current microbiological context in order to provide better care. These infections depend on endogenous and exogenous factors and vary according to the timing of infection, localization and microbiological environment of the patient. There is a high morbidity and mortality associated with these conditions and the treatment must be tailored to patient in question, making it necessary to know the underlying bacteria and the variety of treatment options available. The knowledge of predisposing factors, the high index of suspicion and correct diagnosis and prevention must be performed in all patients and in a multi- disciplinary matter.